Some Chemical Properties and Natural Durability of Samama Wood (Antocephalus macrophylus Roxb.) against Subterranean Termite - Tekat D Cahyono; Syarif Ohorella; Fauzi Febrianto (Masyarakat Peneliti Kayu Indonesia, 2012)
Samama wood (Antocephalus macrophylus Roxb.) is an endemic wood of Sulawesi and Moluccas. This wood belongs to the 3rd class of wood strength. However, its natural durability against termite attack is still unknown. Therefore, the research about its extractives, ash content, heating value, and natural durability is paramount to appropriate usage of the wood. The samples were prepared from samama wood with diameter and height of 30-45 cm and 8.2-11.4 m, respectively. The results indicated that the extractive solubility in hot water, cold water and ethanol benzene were 7.83, 3.86, and 4.47%, respectively. The ash content was 1.31%, meanwhile the heating value was 4059 cal g-1. Based on its weight loss value, according to SNI 01-7207-2006 standard, the natural durability of samama wood against subterranean termite (Coptotermes curvignathus) is classified as in the 2nd class.Key words : Antocephalus macrophylus, extractives, heating value, natural durability, subterranean termite